2007
DOI: 10.1111/j.1742-6723.2007.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of electrocardiogram interpretation improves with emergency medicine training

Abstract: There is an improvement in ECG interpretation accuracy with advancing years of emergency medicine training in Victoria. There exists, however, a low level of accuracy for some critical ECG diagnoses. There is a call by trainees for more formalized and regular ECG education to begin earlier in their training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 17 publications
3
57
0
3
Order By: Relevance
“…The use and interpretation of electrocardiograms (ECGs) is widely accepted as an essential core skill in Emergency Medicine [1]. Electrocardiography is a commonly used procedure for the diagnosis of heart disease—ECG abnormalities may be the first indication of ischaemia, metabolic disturbance, or life-threatening arrhythmia [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use and interpretation of electrocardiograms (ECGs) is widely accepted as an essential core skill in Emergency Medicine [1]. Electrocardiography is a commonly used procedure for the diagnosis of heart disease—ECG abnormalities may be the first indication of ischaemia, metabolic disturbance, or life-threatening arrhythmia [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore imperative that Emergency Physicians are expert in ECG interpretation when they exit their training programme. Specialist emergency physicians are known to improve patient outcomes for patients requiring urgent life saving interventions; previous authors have shown that ECG interpretation skills improve throughout the training programme in Emergency Medicine in Australia [1]. …”
Section: Introductionmentioning
confidence: 99%
“…In order to make a rapid and accurate decision in some diseases such as myocard ischemia, severe electrolyte imbalance or life-threatening serious arrhythmias, clinicians should receive ECG training during their medical education (5).…”
Section: Discussionmentioning
confidence: 99%
“…7,19 Accuracies for the individual ECG diagnoses in our study were similar to those reported in a recent Australian study. 12 The low diagnostic accuracy for some ECG patterns suggests that knowledge deficits may have been just as important as cognitive bias in contributing to diagnostic error. This is supported by the finding that the effect of seniority was similar to that of biased clinical history on the accuracy of ECG interpretation.…”
Section: Discussionmentioning
confidence: 99%